Polytetrafluoroethylene granulated powder and method for producing the same

The use of two silane coupling agents in the PTFE granulation process addresses filler desorption issues, ensuring stable filler adhesion and efficient production of PTFE granules suitable for various applications.

JP2024178027APending Publication Date: 2024-12-24CHEMOURS MITSUI FLUOROPRODUCTS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023096511
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-12
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Existing methods for producing polytetrafluoroethylene (PTFE) granulated powder with metal or metal compound fillers face issues of filler desorption during underwater granulation, especially with hydrophilic surfaces, leading to defective products and loss of filler content.

Method used

A method involving the use of two specific silane coupling agents, a polyhydrolyzable group-type and a monohydrolyzable group-type silane coupling agent, is applied during the mixing and granulation process to enhance filler adhesion, preventing desorption and detachment.

Benefits of technology

The method results in a PTFE granulated powder that is easily handled and maintains filler integrity, facilitating efficient production and use in applications like sliding members and sealing materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024178027000001
    Figure 2024178027000001
  • Figure 2024178027000002
    Figure 2024178027000002
  • Figure 2024178027000003
    Figure 2024178027000003
Patent Text Reader

Abstract

To provide a polytetrafluoroethylene granulated powder that exhibits reduced filler detachment, even when high-specific-gravity metal powder or the like is used as a filler, and a method for producing the same.SOLUTION: A mixture containing a filler, polytetrafluoroethylene powder, a multi-hydrolytic group type silane coupling agent, and a mono-hydrolytic group type silane coupling agent is stirred in a mixture of water and a water-insoluble organic liquid to perform mixing granulation.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a granulated polytetrafluoroethylene powder which is less susceptible to detachment of a filler even when a metal powder or the like having a high specific gravity is used as the filler during production or use, and to a method for producing the same. [Background technology]

[0002] Polytetrafluoroethylene (PTFE) has a low coefficient of friction and excellent heat and chemical resistance, but is susceptible to wear and creep deformation. Therefore, compositions containing various fillers to improve wear and creep resistance are widely used as sliding members and sealing members. PTFE compositions are obtained by mixing PTFE powder with fillers, and granulated powders with high apparent density are produced to improve the handling and powder flowability of the powder. Granulation is also performed on the PTFE powder alone to improve its handling.

[0003] As a method for producing granulated powder, a method in which powder is wetted with an organic solvent to form a slurry and then rolled to granulate (Patent Document 1) is known, but since it is difficult to completely discharge each batch, this method is not preferable in terms of quality when produced continuously. In addition, a method in which a mixture of powder and a non-water-soluble organic solvent is stirred in water (Patent Document 2) is also used because of its good productivity. This method is called underwater granulation. However, this method has a problem in that when a filler particle with a hydrophilic surface is used, the filler is detached in the water. As a result, the detached filler aggregates during the process and gets mixed into the product, causing defective products, and also causes problems such as a loss of filler, which reduces the content ratio below the target value.

[0004] Therefore, methods such as treating hydrophilic fillers with amino group-containing silane (aminosilane) or silicone resin (Patent Document 3), treating hydrophilic fillers with amino group-containing silicone resin (Patent Document 4), and using a specific fluorine-containing solvent as a solvent (Patent Document 5) have been proposed. However, when metal powders or metal compounds (metal salts, metal oxides, etc.) with high surface hydrophilicity and high specific gravity are used as fillers, especially when fillers with small particle sizes are used, detachment occurs even when the above methods are used. Small particle size fillers can provide the effect of the filler even in small amounts, and are therefore preferably used in this respect, but the problem is that they are prone to detachment.

[0005] In addition, although PTFE has excellent non-adhesiveness on the surface, there is also a problem that the filler is easily detached from the obtained granulated powder. This problem occurs not only when a filler with a hydrophilic surface is used, but also when a filler with a hydrophobic surface is used, and it is necessary to improve the adhesion between PTFE and the filler with a hydrophobic surface. In addition, when a filler with a large particle size is used, detachment during granulation is unlikely to occur, but there is also a problem that it is relatively easy to detach from the obtained granulated powder.

[0006] The inventors have found that polyhydrolyzable silane coupling agents having a plurality of specific hydrolyzable silyl groups are effective in suppressing the detachment of fillers, but have also confirmed that they are not necessarily sufficient to suppress the detachment of metal powders that are hydrophilic and have a high specific gravity. For this reason, there is a demand for granulated powders that do not detach during underwater granulation and are easy to handle, even if the filler is a metal powder or a metal compound (such as a metal salt or a metal oxide) that has a highly hydrophilic surface and a high specific gravity. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Special Publication No. 44-22620 [Patent Document 2] Special Publication No. 60-21694 [Patent Document 3] Japanese Patent Application Publication No. 51-549 [Patent Document 4] JP 2001-220482 A [Patent Document 5] JP 2002-201287 A Summary of the Invention [Problem to be solved by the invention]

[0008] An object of the present invention is to provide a granulated powder that is easy to handle and has little loss of filler during production (granulation) or use, even when a metal powder or metal compound is used as a filler. [Means for solving the problem]

[0009] The inventors have discovered that by using two specific silane coupling agents when mixing PTFE powder with a metal powder filler, the detachment of the filler can be significantly reduced and further the detachment of the filler from the resulting granulated powder can be suppressed, thereby completing the present invention.

[0010] One embodiment of the present invention is a method for producing a PTFE composition granulated powder, which is characterized by stirring a mixture containing a filler, a PTFE powder, a polyhydrolyzable silane coupling agent, and a monohydrolyzable silane coupling agent in a mixture of water and a water-insoluble organic liquid to perform mixing and granulation.

[0011] The polyhydrolyzable group-type silane coupling agent is preferably a bis-silane-type silane coupling agent represented by the following formula (1) or a polymer-type silane coupling agent containing a repeating monomer unit represented by the following formula (2). XR 1 -X (1) [X is a hydrolyzable silyl group (-Si(OR 2 ) n (R 3 ) 3-n ) (n = 1 to 3), and R 2 and R 3 are -CH 3Or, -C 2 H 5 and R 1 is a straight-chain or branched-chain hydrocarbon having 2 to 12 carbon atoms, which may contain a substituent and in which hydrogen may be substituted with a halogen.]

[0012] [ka] [X is a hydrolyzable silyl group (-Si(OR 2 ) n (R 3 ) 3-n ) (n = 1 to 3), and R 2 and R 3 are -CH 3 Or, -C 2 H 5 and A is CH or N; R a and R b each independently represents a hydrocarbon having 1 to 10 carbon atoms which may contain a substituent and in which hydrogen may be substituted with a halogen, R c is a hydrocarbon having 1 to 5 carbon atoms, in which hydrogen may be substituted with a halogen, p=3~30.

[0013] The monohydrolyzable group-type silane coupling agent is preferably a silane coupling agent represented by the following formula (3). XR 4 (3) [X is a hydrolyzable silyl group (-Si(OR 2 ) n (R 3 ) 3-n ) (n = 1 to 3), and R 2 and R 3 are -CH 3 Or, -C 2 H 5 and R 4is a straight-chain or branched-chain hydrocarbon having 2 to 12 carbon atoms, which may contain a substituent and in which hydrogen may be substituted with a halogen.]

[0014] The filler is preferably a filler having a hydrophilic surface, and is more preferably a metal or a metal oxide.

[0015] Another embodiment of the present invention is a composition comprising 3 to 40 volume percent of a filler. A granulated powder comprising 60 to 97 volume % polytetrafluoroethylene powder, The polytetrafluoroethylene granulated powder contains 1 part by mass or less of a polyhydrolyzable group-type silane coupling agent and a monohydrolyzable group-type silane coupling agent per 100 parts by mass of the total of a filler and the polytetrafluoroethylene powder.

[0016] The polyhydrolyzable group-type silane coupling agent is preferably a bis-silane-type silane coupling agent represented by formula (1) or a polymeric silane coupling agent containing a repeating monomer unit represented by formula (2). XR 1 -X (1) [X is a hydrolyzable silyl group (-Si(OR 2 ) n (R 3 ) 3-n ) (n = 1 to 3), and R 2 and R 3 are -CH 3 Or, -C 2 H 5 and R 1 is a straight-chain or branched-chain hydrocarbon having 2 to 12 carbon atoms, which may contain a substituent and in which hydrogen may be substituted with a halogen.]

[0017] [ka] [X is a hydrolyzable silyl group (-Si(OR 2 ) n (R 3 ) 3-n ) (n = 1 to 3), and R2 and R 3 are -CH 3 Or, -C 2 H 5 and A is CH or N; R a and R b each independently represents a hydrocarbon having 1 to 10 carbon atoms which may contain a substituent and in which hydrogen may be substituted with a halogen, R c is a hydrocarbon having 1 to 5 carbon atoms, in which hydrogen may be substituted with a halogen, p=3~30.

[0018] The monohydrolyzable group-type silane coupling agent is preferably a silane coupling agent represented by the following formula (3). XR 4 (3) [X is a hydrolyzable silyl group (-Si(OR 2 ) n (R 3 ) 3-n ) (n = 1 to 3), and R 2 and R 3 are -CH 3 Or, -C 2 H 5 and R 4 is a straight-chain or branched-chain hydrocarbon having 2 to 12 carbon atoms, which may contain a substituent and in which hydrogen may be substituted with a halogen.]

[0019] The average particle size of the granulated powder is preferably 200 to 800 μm.The filler is preferably a filler having a hydrophilic surface, and is more preferably a metal or a metal oxide. Effect of the Invention

[0020] The PTFE granulated powder of the present invention can be produced by a highly productive underwater granulation method. In addition, the production method of the PTFE granulated powder of the present invention allows granulation in which the filler is not desorbed into the aqueous phase and is uniformly dispersed, even when a hydrophilic filler such as a metal powder is used. The obtained granulated powder is easy to handle and does not easily desorb the filler, so it is easy to produce molded products by compression molding and can be used for various applications such as sliding members and sealing materials. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The PTFE granulated powder of the present invention is produced from a filler, a PTFE powder, and two specific silane coupling agents. First, each component will be described below.

[0022] (1) Polytetrafluoroethylene (PTFE) The PTFE powder used in the present invention may be a homopolymer of tetrafluoroethylene (TFE) (homo-PTFE), a TFE copolymer (modified PTFE) containing 1% by weight or less of a monomer copolymerizable with TFE, or a mixture thereof.

[0023] As the monomer (comonomer) copolymerizable with TFE contained in the modified PTFE, a monomer containing an unsaturated bond and capable of radical polymerization can be used. In order to maintain the excellent performance of PTFE, such as heat resistance and chemical resistance, it is preferable to use a fluorine-containing monomer as the comonomer. Specific examples of the comonomer include perfluoroalkene having 3 or more carbon atoms, preferably 3 to 6 carbon atoms, perfluoro(alkyl vinyl ether) having 1 to 6 carbon atoms, and chlorotrifluoroethylene. Among these, it is preferable to use hexafluoropropylene (HFP), perfluoro(methyl vinyl ether) (PMVE), perfluoro(ethyl vinyl ether) (PEVE), perfluoro(propyl vinyl ether) (PPVE), and perfluoro(butyl vinyl ether) (PBVE), and chlorotrifluoroethylene.

[0024] When modified PTFE is used, the presence of the comonomer makes it difficult for molecular chains to slide against each other, so that the strength and elastic modulus of the resin are increased and creep resistance is improved. However, if the amount of the comonomer exceeds 1% by weight, the sliding properties of PTFE are reduced and the material becomes fluid at temperatures above its melting point, making it unsuitable for use at high temperatures. In addition, it becomes difficult to produce molded products by the free baking method, in which a compression-molded composition is heated and baked at temperatures above its melting point. For this reason, the comonomer content is preferably in the range of 0.001 to 1% by weight of comonomer units.

[0025] As a polymerization method for PTFE, known polymerization methods such as suspension polymerization and emulsion polymerization can be used. For the resin composition of the present invention, powdered PTFE (molding powder) obtained by suspension polymerization is preferably used for the following reasons. Compared with PTFE obtained by emulsion polymerization, PTFE obtained by suspension polymerization is less likely to cause fibrosis due to shear stress, so dry mixing at room temperature is possible. In addition, suspension polymerization is excellent in terms of handling because the powder does not solidify even during the input work at the time of molding, and is also excellent in terms of low cost.

[0026] PTFE can be used as a molding material if it has a molecular weight that allows it to be molded by means of compression molding, etc. It is known that the melting point of PTFE correlates with the molecular weight, and a polymer with a melting point of about 327°C can be suitably used as a molding resin for sliding parts with good mechanical strength and heat resistance.

[0027] Moreover, this PTFE is usually used in a powder state for molding various products. Its average particle size is 100 μm or less, preferably 5 to 100 μm, and more preferably in the range of 10 to 50 μm. PTFE powder with an average particle size in this range is excellent in uniform mixing with various fillers. Such PTFE can be directly manufactured in a powder form by a suspension polymerization method. Also, commercially available molding powders can be used as long as they have such an average particle size.

[0028] Examples of such PTFE molding powders include Teflon (registered trademark) PTFE 7-J (homo PTFE, average particle size: 50 μm) manufactured by Mitsui-Chemours Fluoroproducts, Inc., Teflon (registered trademark) PTFE 7A-J (homo PTFE, average particle size: 30 μm) manufactured by Mitsui-Chemours Fluoroproducts, Inc., and Teflon (registered trademark) PTFE 70-J (modified PTFE, average particle size: 35 μm) manufactured by Mitsui-Chemours Fluoroproducts, Inc.

[0029] (2) Filling material In the present invention, the "filler" refers to a powdery substance used to improve various physical properties of a molded product, and the filler used in the present invention includes various organic and inorganic substances mixed with the PTFE powder for molding. Examples of organic substances include engineering plastics such as polyphenylene sulfide, polyethersulfone, polyphenylsulfone, polyamide, polyimide, phenolic resin, urea resin, epoxy resin, urethane resin, melamine resin, polyester resin, polyether resin, acrylic resin, acrylic silicone resin, silicone resin, and silicone polyester resin. Examples of inorganic substances include metals, metal oxides (aluminum oxide, zinc oxide, tin oxide, titanium oxide (titanate), etc.), glass, ceramics, silicon carbide, silicon oxide, calcium fluoride, carbon black, carbon fiber, graphite, coke, mica, talc, barium sulfate, and molybdenum disulfide. If necessary, a combination of these substances can also be used.

[0030] In the present invention, fillers having hydrophilic particle surfaces, which have been difficult to handle in the underwater granulation method, can also be used. Specific examples of fillers having hydrophilic particle surfaces include metals (bronze, aluminum, etc.), metal compounds (metal oxides, metal salts, metal halides), inorganic salts (silicon carbide, silicon oxide, boron nitride, calcium fluoride, etc.), glass, and silica. In the present invention, by using a specific silane coupling agent, even fillers having hydrophilic particle surfaces can be prevented from being detached due to migration of the filler to the aqueous phase during underwater granulation, and detachment can be suppressed even for fillers having a large specific gravity such as metals and metal compounds, which are particularly likely to migrate to the aqueous phase during underwater granulation. In the present invention, as described below, by using two types of specific silane coupling agents, even when fillers having hydrophilic surfaces, more specifically, metals or metal oxides, are used as fillers, their detachment can be sufficiently suppressed.

[0031] In addition, particles of engineering plastics with hydrophobic surfaces such as fully aromatic polyester resins, and carbon-based fillers with graphene structures with hydrophobic particle surfaces such as carbon black, carbon fiber, graphite, and coke may be used, and the use of a specific silane coupling agent allows the filler to be attached to the granulated powder with sufficient strength, and detachment of the filler due to vibration or the like can be suppressed in the process after granulation or when the granulated powder is used. Furthermore, the use of a silane coupling agent having a polar functional group also provides the effect of preventing static electricity from being charged in the granulated powder.

[0032] The particle shape of the filler can be various shapes such as particles, fibers, and flakes, and any shape can be used. If the particle size is small, even a small amount of the filler can improve the physical properties, but there is a problem that the filler is easily transferred into water during underwater granulation. In the present invention, a specific silane coupling agent is used to suppress the detachment of the small particle size filler whose surface is hydrophilic, so that a small particle size filler of 0.1 μm to 100 μm can also be used.

[0033] However, from the viewpoint of efficiently producing granulated particles of good quality, the average particle size of the filler is preferably 1 μm to 500 μm, and more preferably 3 μm to 300 μm. The average particle size of the filler means the particle size at an integrated value of 50% (volume basis) in the particle size distribution measured by a laser diffraction / scattering method.

[0034] (3) Two types of silane coupling agents The present invention is characterized by including two types of silane coupling agents, that is, a polyhydrolyzable silane coupling agent (also referred to as "silane coupling agent 1") and a monohydrolyzable silane coupling agent (also referred to as "silane coupling agent 2"). By including these two types of silane coupling agents, even when a filler having a hydrophilic surface such as a metal or metal oxide is used, which was previously difficult, the detachment can be sufficiently suppressed.

[0035] (3-1) Polyhydrolyzable silane coupling agents (Silane coupling agent 1) Generally, a silane coupling agent is a compound having a hydrolyzable silyl group, as shown in formula (4) below, which reacts with an inorganic material to form a covalent bond.

[0036] R-Si(OR 2 ) n (R 3 ) 3-n (n=1-3) (4)

[0037] R 2 , R 3 are each independently a methyl group or an ethyl group, and R is called an organic substituent, and is a saturated or unsaturated alkyl group which may contain one or more reactive groups, such as a vinyl group, an epoxy group (alicyclic epoxy group, glycidyl group), a methacryl group, an acryl group, a styryl group, an amino group, an imino group, a sulfide group, a disulfide group, an aryl group, a diamino group, a mercapto group, a ureido group, or an isocyanate group, depending on the desired properties.

[0038] The polyhydrolyzable group-type silane coupling agent used in the present invention has a hydrolyzable silyl group: -Si(OR 2 ) n (R 3 ) 3-n ) (n=1 to 3). Specific examples of the polyhydrolyzable group type silane coupling agent include bis-silane type silane coupling agents having a structure in which an organic substituent has hydrolyzable silyl groups at both ends, and polymer type silane coupling agents having a structure in which an organic substituent is a polymer having a repeating structure and has a hydrolyzable silyl group at its side chain, and it is preferable to use these.

[0039] (3-1-1) Bis-silane type silane coupling agents The bis-silane type silane coupling agent used in the present invention is a compound having two hydrolyzable silyl groups in the molecule and represented by the following formula (1).

[0040] XR 1 -X (1)

[0041] X is a hydrolyzable silyl group [-Si(OR 2 ) n (R 3 ) 3-n ] (n=1 to 3), preferably a trialkoxysilyl group: -Si(OR 2 ) 3 or a dialkoxysilyl group: -SiR 3 (OR 2 ) 2 R 2 and R 3 Each represents an alkyl group, preferably -CH 3 Or, -C 2 H 5 A trialkoxysilyl group in which n=3 is preferred, and a trimethoxysilyl group is more preferred.

[0042] R 1R is a straight-chain or branched-chain hydrocarbon having 2 to 12 carbon atoms, which may contain a substituent and may have hydrogen substituted with a halogen. The number of carbon atoms of the hydrocarbon is preferably 5 to 10, and the hydrocarbon is preferably straight-chain. The larger the number of carbon atoms of the hydrocarbon, the higher the hydrophobicity becomes, and the better the affinity with PTFE, which is preferable. 1 It is considered that the affinity with PTFE is improved by the stronger hydrophobicity, and the effect of suppressing the detachment of the filler into the aqueous phase is also high, so that it is preferable that the filler does not have a substituent. When a substituent is present, the substituent is, for example, -NH- (imino group), -S-, -SS-, -C 6 H 4 - etc., or may contain a carbonyl group. Having a polar functional group (imino group, carbonyl group, etc.) in the molecule can contribute to antistatic, which results in improved water solubility of the molecule and can be effective with many fillers in small amounts, improving mixing during granulation. Hydrogen in the hydrocarbon may be substituted with a halogen, for example, chlorine, etc.

[0043] Specific examples of the bissilane type silane coupling agent include, but are not limited to, 1,2-bis(triethoxysilyl)ethane, 1,2-bis(triethoxysilyl)ethylene, 1,6-bis(trimethoxysilyl)hexane, 1,8-bis(trimethoxysilyl)octane, 1,8-bis(triethoxysilyl)octane, bis[3-tri(methoxysilyl)propyl]amine, bis[3-tri(ethoxysilyl)propyl]amine, N,N'-bis[3-tri(methoxysilyl)propyl]ethylenediamine, 1,4-bis(trimethoxysilylethyl)benzene, 1,3-bis(trimethoxysilylpropyl)benzene, 1,6-bis(trimethoxysilyl)-2,5-dimethylhexane, bis(triethoxysilylpropyl)disulfide, and mixtures of two or more selected from these. Among these, 1,6-bis(trimethoxysilyl)hexane, 1,8-bis(trimethoxysilyl)octane, or bis[3-tri(methoxysilyl)propyl]amine is preferred, and 1,8-bis(trimethoxysilyl)octane is more preferred. The bissilane-type silane coupling agent used in the present invention has two or more hydrolyzable silyl groups, and is therefore considered to act to bind with the filler to be mixed and inhibit its separation.

[0044] Such bis-silane type silane coupling agents can be produced by the methods described in JP-A-5-194551, JP-T-2005-509683, or US6242627. Alternatively, commercially available agents such as SIB1824.0 and SIB1832.7 manufactured by Gelest, Inc., Dynasilane 1124 manufactured by Evonik Industries AG, and KBM-3086 manufactured by Shin-Etsu Chemical Co., Ltd. can be used.

[0045] (3-1-2) Polymeric silane coupling agents The polymeric silane coupling agent is a silane coupling agent containing a repeating monomer unit of the following formula (2).

[0046] [ka]

[0047] X is a hydrolyzable silyl group (-Si(OR 2 ) n (R 3 ) 3-n ) (n=1 to 3), preferably a trialkoxysilyl group: -Si(OR 2 ) 3 or a dialkoxysilyl group: -SiR 3 (OR) 2 R 2 and R 3 Each represents an alkyl group, preferably -CH 3 Or, -C 2 H 5 A is preferably a trialkoxysilyl group in which n=3, and more preferably a trimethoxysilyl group. A is CH or N.

[0048] R a and R b R are each independently a hydrocarbon having 1 to 10 carbon atoms, which may contain a substituent and in which hydrogen may be substituted with a halogen, preferably having 2 to 8 carbon atoms, and more preferably having 2 to 6 carbon atoms. If the hydrocarbon has 2 or more carbon atoms, it is preferable because it is believed that the hydrophobicity is enhanced and the affinity with PTFE is improved. a and R b R having no substituent is preferable because it is believed that this will increase hydrophobicity, improve affinity with PTFE, and increase the effect of suppressing the detachment of the filler into the aqueous phase. a and R b In the main skeleton, -NH- (imino group), -S-, -SS-, -C 6 H 4 - and may contain substituents such as acrylic, epoxy, and mercapto groups as side chains. Having polar functional groups (imino, acrylic, epoxy, etc.) in the molecule can contribute to antistatic properties, which results in improved water solubility of the molecule and the effect can be obtained with a small amount for many fillers, improving mixing during granulation. cis a hydrocarbon having 1 to 5 carbon atoms in which hydrogen may be substituted with a halogen, and is preferably a straight-chain hydrocarbon.

[0049] The molecular weight of the polymeric silane coupling agent depends on the molecular structure of the basic skeleton, but is, for example, 500 to 5000, preferably 900 to 3000, and more preferably 1200 to 2000. The degree of polymerization p of the polymeric silane coupling agent depends on the molecular structure of the basic unit, but is, for example, 3 to 30, preferably 3 to 20, and more preferably 3 to 10.

[0050] As a specific example, a trimethoxysilylpropyl-modified polyethyleneimine can be mentioned as a polymeric silane coupling agent, and a modified polyethyleneimine polymer having a base unit of the following formula (5) can be mentioned.

[0051] [ka]

[0052] The amine moiety in the above polymer unit becomes an ammonium ion and can be substituted with any anion (e.g., Cl - ) may form a salt.

[0053] Examples of various polymeric silane coupling agents having such hydrolyzable silyl group side chains include X-12-1048, X-12-1050, and X-12-972F manufactured by Shin-Etsu Chemical Co., Ltd., and SSP-060, SSP-065, and SSP-050 manufactured by Gelest, Inc.

[0054] The polymeric silane coupling agent used in the present invention has multiple hydrolyzable silyl groups, and therefore acts to bind with the mixed filler and / or PTFE to suppress their separation. In addition, since it has a hydrophobic polymer main chain, it is believed that detachment of the filler due to migration into the aqueous phase during the granulation process is suppressed.

[0055] The silane coupling agent used in the present invention, especially one having a polar functional group, is considered to not only strengthen the adhesion between the PTFE and the filler, but also to provide an antistatic effect to the particles after granulation, which is considered to make the granulated particles less likely to clog the sieve.

[0056] The silane coupling agent used in the present invention is preferably used as a solution dissolved in a solvent in order to disperse uniformly in the mixing process.The solvent is not particularly limited, but can be, for example, toluene, isopropyl alcohol, 1,3-dichloro-1,1,2,2,3-pentafluoropropane, 1-chloro-2,3,3-trifluoropropene, and other various organic solvents, and can be, for example, 1-chloro-2,3,3-trifluoropropene.

[0057] (3-2) Monohydrolyzable silane coupling agents (Silane coupling agents 2) The present invention is characterized in that it contains a monohydrolyzable silane coupling agent (silane coupling agent 2) in addition to the polyhydrolyzable silane coupling agent (silane coupling agent 1) described above. The monohydrolyzable silane coupling agent of the present invention is a silane coupling agent having one hydrolyzable silyl group in the molecule. Specifically, it is preferably a compound represented by the following formula (3).

[0058] XR 4 (3) [X is a hydrolyzable silyl group (-Si(OR 2 ) n (R 3 ) 3-n ) (n = 1 to 3), and R 2 and R 3 are -CH 3 Or, -C 2 H 5 and R 4 is a straight-chain or branched-chain hydrocarbon having 2 to 12 carbon atoms, which may contain a substituent and in which hydrogen may be substituted with a halogen.]

[0059] The number of carbon atoms of the hydrocarbon is preferably 4 to 8, and the hydrocarbon is preferably linear. The more carbon atoms of the hydrocarbon, the higher the hydrophobicity becomes, and the better the affinity with PTFE, which is preferable. 4 Those having no substituents are preferred because the affinity with PTFE is improved by the stronger hydrophobicity, and the detachment of the filler into the aqueous phase is suppressed. When a substituent is present, the substituent may be present between the carbon-carbon of the hydrocarbon as a divalent group such as -NH- (imino group), -O-, -C(=O)- (carbonyl group), or may be present as a polar functional group such as an amino group, an epoxy group, an acrylic group, a mercapto group, an isocyanate group, or a ureido group as an end group. Among them, those containing any of a carbonyl group (-C(=O)-), an amino group, an imino group, an epoxy group, and an acrylic group as a substituent are preferred. It can contribute to antistatic, and as a result, the water solubility of the molecule is improved, and the effect can be obtained with a small amount for many fillers, so that mixing during granulation is improved. The hydrogen of the hydrocarbon may be substituted with a halogen, for example, chlorine, etc.

[0060] Specific examples of the monohydrolyzable group type silane coupling agent include, but are not limited to, a mixture of two or more selected from 3-acryloxypropyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3,3,3-trifluoropropyltrimethoxysilane, etc. Among these, 3-acryloxypropyltrimethoxysilane or 3-methacryloxypropyltrimethoxysilane is preferred.

[0061] As such a monohydrolyzable silane coupling agent, for example, KBM-5103, KBM-503, KBM-403, KBM-603, KBM-7103, etc. manufactured by Shin-Etsu Chemical Co., Ltd. can be used.

[0062] (4) Granulated powder of the present invention and its manufacturing method The granulated powder of the present invention is made from a mixture containing a filler, polytetrafluoroethylene (PTFE) powder, and a polyhydrolyzable silane coupling agent. The composition ratio of PTFE:filler is 99-20% by volume:1-80% by volume, preferably 97-60% by volume:3-40% by volume, and more preferably 94-75% by volume:6-25% by volume. If the content of the filler in this mixture is low, it becomes difficult to obtain the effect of improving the physical properties by the filler, while if the content of the filler is too high, the physical properties such as elongation of the molded product manufactured from the obtained granulated powder are reduced.

[0063] The content of the silane coupling agent used in the present invention is preferably 0.001 to 1.0 parts by mass, more preferably 0.01 to 0.3 parts by mass, and even more preferably 0.01 to 0.2 parts by mass, based on 100 parts by mass of the total of the filler and the polytetrafluoroethylene powder. A low concentration of 0.02 to 0.1 parts by mass is also acceptable. The content of the silane coupling agent means the total amount of the silane coupling agent 1 and the silane coupling agent 2. With regard to the ratio of the silane coupling agent 1 to the silane coupling agent 2, the content of the silane coupling agent 1 is preferably less than the content of the silane coupling agent 2. The ratio of the silane coupling agent 1 to the silane coupling agent 2 is preferably about 1:1 to 1:3 (mass ratio), since a sufficient effect of suppressing the detachment of the filler can be obtained. In addition, other additives can be added to the mixture as optional components.

[0064] Examples of additives include one or more of solid lubricants, oxidation stabilizers, heat stabilizers, wear-resistant materials, weather stabilizers, flame retardants, and pigments, and these may be contained within a range that does not affect the physical properties of the granulated particles (for example, 5% by weight or less).

[0065] As a method for mixing the filler, polytetrafluoroethylene (PTFE) powder, and two kinds of silane coupling agents, the PTFE powder and the filler are mixed to form a mixed powder, and the mixed powder is treated with a solution containing the silane coupling agent. Alternatively, the filler may be mixed with a solution containing the silane coupling agent to perform surface treatment, and then mixed with the PTFE powder. The PTFE powder, the filler, and the solution of the silane coupling agent may be mixed at the same time to produce the silane coupling agent.

[0066] The granulated powder of the present invention is produced from the above mixture by various known granulation methods, but is preferably produced by underwater granulation. As a specific underwater granulation method, a mixture containing a filler, a PTFE powder, and two types of silane coupling agents can be added to a mixed liquid of a water-insoluble organic liquid and water, and stirred. Alternatively, the water-insoluble organic liquid and the above mixture may be mixed to obtain a slurry, and the slurry may be stirred at high speed with a large amount of water to granulate. Thereafter, the granulated powder can be taken out of the water and dried to obtain a granulated powder. The granulated powder may be produced by adding a surfactant to the water during high-speed stirring in water. Furthermore, the granulated particles of the present invention can also be produced by using composite particles obtained by mixing a PTFE aqueous dispersion obtained by emulsion polymerization with a filler.

[0067] The water-insoluble organic liquid used in the present invention can be various organic solvents that have low surface energy and are incompatible with water, and examples of such organic solvents include hydrocarbons such as hexane, kerosene, cyclohexane, benzene, toluene, and xylene, ethers such as diethyl ether and dipropyl ether, halogenated hydrocarbons such as methylene chloride, dichloroethylene, trichloroethylene, tetrachloroethylene, chlorobenzene, dichlorobenzene, fluorotrichloromethane, fluorodichloroethane, dichlorotrifluoroethane, trichlorotrifluoroethane, difluorotetrachloroethane, dichloropentafluoropropane, and decafluoropentane, and fluoroethers such as perfluoropropyl methyl ether, perfluorobutyl methyl ether, perfluorobutyl ethyl ether, perfluoropentyl methyl ether, and perfluoropentyl ethyl ether. Two or more of these can also be used in combination.

[0068] The average particle size of the granulated powder of the present invention is preferably 200 μm to 800 μm. If it is too large, voids remain when compression molded, deteriorating the tensile and compressive properties. If it is too small, the filler that has come off the particles of the granulated powder will aggregate, easily causing defects. In the present invention, the average particle size of the granulated powder means the particle size of the cumulative 50% (by weight) in a dry sieving test. EXAMPLES

[0069] The present invention will be specifically described below with reference to examples. The raw materials used in the examples and comparative examples and the methods for evaluating the obtained PTFE molding powder are as follows.

[0070] 1.Raw materials (a) PTFE raw material powder: Teflon (registered trademark) PTFE 7-J (homo PTFE, average particle size: 50 μm) manufactured by Mitsui-Chemours Fluoro Products Co., Ltd. (b) Filler: Bronze powder (AtW-350, manufactured by Fukuda Metal Foil and Powder Co., Ltd., average particle size: 30 μm)

[0071] (c) Silane coupling agent:

[0072] [Table 1]

[0073] [Table 2]

[0074] 2. Physical property evaluation method (a) Measurement of the amount of filler detached In the examples and comparative examples described later, the wastewater (about 15 L) from the sieve used to collect the granulated powder was collected in a bucket, and the sealed container with a stirrer used for granulation was rinsed with about 10 L of pure water, which was then placed in the same bucket and left to stand for 60 minutes to allow the detached filler (bronze powder) to settle. Meanwhile, the PTFE molding powder floating on the water surface and the water layer that became transparent due to the saturation of the filler were removed as much as possible from the bucket, and the remaining layer of the saturation of the filler was transferred to a glass petri dish and dried by heating in an oven at 170°C for 11 hours. The weight of the dried filler (bronze) was measured with an electronic balance. In each example and comparative example, the degree of detachment (amount of detached filler / amount of added filler) was calculated using the amount of added filler. (b) Average particle size of granulated powder Using a Seishin Enterprise Co., Ltd. RPS-02 model, measurements were taken using eight standard sieves (ASTM E11) of 14, 16, 20, 28, 35, 48, 70, and 100 mesh (from top to bottom) stacked in order, and the weight of the powder remaining on each sieve was determined. Based on these weights, the particle sizes of 16%, 50%, and 84% by weight were calculated.

[0075] <1> When a bis-silane type silane coupling agent was used as the silane coupling agent 1 (Example 1) PTFE molding powder (trade name Teflon (registered trademark) 7-J, melting point 327 ° C.) and bronze powder were each put into a Henschel mixer so that PTFE was 60% by weight (85.7% by volume) and bronze powder was 40% by weight (14.3% by volume), totaling 4.5 kg, and mixed for 5 minutes, then 40 g of pure water was added and mixed for another 15 minutes. Next, a solution of 2.3 g of bis[3-(trimethoxysilyl)propyl]amine (bissilane type silane coupling agent B-1) as silane coupling agent 1 and 4.5 g of 3-acryloxypropyltrimethoxysilane (monohydrolyzable group type silane coupling agent M-1) as silane coupling agent 2 dissolved in 40 g of 1-chloro-2,3,3-trifluoropropene (AMOLEA (registered trademark) AS-300 manufactured by AGC Co., Ltd.) was added as silane coupling agent 1, and mixed for 55 minutes to obtain a uniform mixture.

[0076] 15L of water was added to a 50L sealed container equipped with a stirrer, and the temperature was kept at 70℃. The mixture obtained above was added, and 40 parts by weight of tetrachloroethylene was added per 100 parts by weight of the mixture. The mixture was stirred at 500 rpm for 5 minutes, then the rotation speed was reduced to 350 rpm, and the mixture was stirred for a further 35 minutes and granulated. The liquid phase was separated using a 150 mesh sieve (the amount of filler detached was measured as described above for the wastewater), and the mixture was dried in an oven at 170℃ for 11 hours to obtain a granulated powder.

[0077] Example 2 A granulated powder was obtained in the same manner as in Example 1, except that 3-methacryloxypropyltrimethoxysilane (monohydrolyzable silane coupling agent M-2) was used as the silane coupling agent 2 instead of 3-acryloxypropyltrimethoxysilane (monohydrolyzable silane coupling agent M-1).

[0078] Example 3 A granulated powder was obtained in the same manner as in Example 1, except that 3-glycidoxypropyltrimethoxysilane (monohydrolyzable silane coupling agent M-3) was used as the silane coupling agent 2 instead of 3-acryloxypropyltrimethoxysilane (monohydrolyzable silane coupling agent M-1).

[0079] Example 4 A granulated powder was obtained in the same manner as in Example 1, except that, as the silane coupling agent 2, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane (monohydrolyzable silane coupling agent M-4) was used instead of 3-acryloxypropyltrimethoxysilane (monohydrolyzable silane coupling agent M-1).

[0080] Example 5 A granulated powder was obtained in the same manner as in Example 1, except that 3,3,3-trifluoropropyltrimethoxysilane (monohydrolyzable silane coupling agent M-5) was used as the silane coupling agent 2 instead of 3-acryloxypropyltrimethoxysilane (monohydrolyzable silane coupling agent M-1).

[0081] Example 6 Granulated powder was obtained in the same manner as in Example 1, except that 1,8-bis(trimethoxysilyl)octane (bissilane type silane coupling agent B-2) was used as the silane coupling agent 1 instead of bis[3-(trimethoxysilyl)propyl]amine (bissilane type silane coupling agent B-1).

[0082] Comparative Example 1 A granulated powder was obtained in the same manner as in Example 1, except that only 6.8 g of bis[3-(trimethoxysilyl)propyl]amine (bissilane-type silane coupling agent B-1) was used as the silane coupling agent.

[0083] The compositions and results of Examples 1 to 6 and Comparative Example 1 are summarized in Table 3 below. In Comparative Example 1, in which only the bis-silane type silane coupling agent B-1 was used as the silane coupling agent, the degree of detachment in the granulation wastewater was 3.9%, and a large amount of detached filler was confirmed by visual evaluation. On the other hand, in Examples 1 to 4, in which two types of silane coupling agents (silane coupling agents 1 and 2) were used in combination, the degree of detachment in the granulation wastewater was significantly reduced, and almost no detached filler was confirmed by visual evaluation. In Example 5, in which the monohydrolyzable silane coupling agent M-5 was used as the silane coupling agent 2, the degree of detachment in the granulation wastewater was reduced to 2.1%. In Example 6, in which the bis-silane type silane coupling agent B-2 was used as the silane coupling agent 1, the degree of detachment in the granulation wastewater was reduced to 1.4%.

[0084] [Table 3]

[0085] <2> When a polymeric silane coupling agent is used as silane coupling agent 1 Example 7 PTFE molding powder (trade name Teflon (registered trademark) 7-J, melting point 327 ° C.) and bronze powder were each put into a Henschel mixer so that PTFE was 60% by weight (85.7% by volume) and bronze powder was 40% by weight (14.3% by volume), totaling 4.5 kg, and mixed for 5 minutes, then 40 g of pure water was added and mixed for another 15 minutes. Next, a solution of 2.3 g of trimethoxysilylpropyl modified polyethyleneimine (polymer type silane coupling agent P-1) as silane coupling agent 1 and 4.5 g of 3-acryloxypropyltrimethoxysilane (monohydrolyzable group type silane coupling agent M-1) as silane coupling agent 2 dissolved in 40 g of 1-chloro-2,3,3-trifluoropropene (AMOLEA (registered trademark) AS-300 manufactured by AGC Co., Ltd.) was added as silane coupling agent 1 and mixed for 55 minutes to obtain a uniform mixture.

[0086] 15L of water was added to a 50L sealed container equipped with a stirrer, kept at 70℃, the mixture obtained above was poured in, 40 parts by mass of tetrachloroethylene was added per 100 parts by mass of the mixture, and the mixture was stirred at 500 rpm for 5 minutes, then the rotation speed was reduced to 350 rpm and stirred for a further 35 minutes to granulate. The liquid phase was separated using a 150 mesh sieve (the above-mentioned filler detachment amount measurement was performed on the wastewater), and the mixture was dried in an oven at 170℃ for 11 hours to obtain a granulated powder.

[0087] Example 8 A granulated powder was obtained in the same manner as in Example 7, except that 3-methacryloxypropyltrimethoxysilane (monohydrolyzable silane coupling agent M-2) was used as the silane coupling agent 2 instead of 3-acryloxypropyltrimethoxysilane (monohydrolyzable silane coupling agent M-1).

[0088] Example 9 A granulated powder was obtained in the same manner as in Example 7, except that 3-glycidoxypropyltrimethoxysilane (monohydrolyzable silane coupling agent M-3) was used as the silane coupling agent 2 instead of 3-acryloxypropyltrimethoxysilane (monohydrolyzable silane coupling agent M-1).

[0089] Example 10 A granulated powder was obtained in the same manner as in Example 7, except that the amount of silane coupling agent 1 was changed to 0.9 g and the amount of silane coupling agent 2 was changed to 2.3 g.

[0090] Example 11 A granulated powder was obtained in the same manner as in Example 7, except that the amount of silane coupling agent 1 was changed to 0.5 g and the amount of silane coupling agent 2 was changed to 0.9 g.

[0091] Example 12 A granulated powder was obtained in the same manner as in Example 7, except that a different polymeric silane coupling agent P-2 (Shin-Etsu Chemical Co., Ltd. X-12-1050) was used as the silane coupling agent 1 instead of trimethoxysilylpropyl-modified polyethyleneimine (polymeric silane coupling agent P-1).

[0092] Comparative Example 2 A granulated powder was obtained in the same manner as in Example 7, except that only 6.8 g of trimethoxysilylpropyl-modified polyethyleneimine (polymeric silane coupling agent P-1) was used as the silane coupling agent.

[0093] The compositions and results of Examples 7 to 12 and Comparative Example 2 are summarized in Table 4 below. In Comparative Example 2, in which only the polymeric silane coupling agent P-1 was used, the degree of detachment in the granulation wastewater was 16.0%, which was very high, and a large amount of detached filler was confirmed by visual evaluation. On the other hand, in Examples 7 to 9, in which two types of silane coupling agents (silane coupling agents 1 and 2) were used in combination, the degree of detachment in the granulation wastewater was significantly reduced, and it was confirmed by visual evaluation that the amount of detached filler was significantly reduced.

[0094] Among these, the effect of Example 7, in which the monohydrolyzable silane coupling agent M-1 was used as the silane coupling agent 2, was particularly outstanding. The effect of suppressing the detachment of the filler was confirmed to be as remarkable as that of Examples 10 and 11, in which the amount of the silane coupling agents (silane coupling agents 1 and 2) added was reduced. Also, the effect of suppressing the detachment of the filler was confirmed to be high in Example 12, in which the monohydrolyzable silane coupling agent M-1 was used as the silane coupling agent 2 and the silane coupling agent 1 was replaced with the polymeric silane coupling agent P-2.

[0095] [Table 4]

[0096] The particle size distribution (d16, d50 and d84) of some of the granulated powders produced in the above Examples and Comparative Examples was measured, and the results are as follows: In all of Examples 6 and 10-12 and Comparative Examples 1 and 2, powders having particle sizes in the distribution range of about 200 to 800 μm could be granulated.

[0097] [Table 5] [Industrial Applicability]

[0098] The method for producing the granulated powder of the present invention can reduce the detachment of the filler from the granulated powder. The method for producing the granulated powder of the present invention is an underwater granulation method, so that the granulated powder can be produced efficiently with high productivity. The PTFE granulated powder of the present invention can be easily produced into molded products by compression molding, and can be used for various applications such as sliding members and sealing materials.

Claims

1. A method for producing polytetrafluoroethylene granulated powder, comprising stirring a mixture containing a filler, polytetrafluoroethylene powder, a polyhydrolyzable silane coupling agent, and a monohydrolyzable silane coupling agent in a mixture of water and a water-insoluble organic liquid to perform mixing and granulation.

2. The method for producing a granulated powder according to claim 1, wherein the polyhydrolyzable group-type silane coupling agent is a bis-silane-type silane coupling agent represented by the following formula (1) or a polymeric silane coupling agent containing a repeating monomer unit represented by the following formula (2). X-R 1 -X (1) [X is a hydrolyzable silyl group (-Si(OR 2 ) n (R 3 ) 3-n ) (n=1 to 3), R 2 and R 3 are -CH 3 Or, -C 2 H 5 and R 1 is a straight-chain or branched-chain hydrocarbon having 2 to 12 carbon atoms, which may contain a substituent and in which hydrogen may be replaced by a halogen. 【Chemistry 1】 [X is a hydrolyzable silyl group (-Si(OR 2 ) n (R 3 ) 3-n ) (n=1 to 3), R 2 and R 3 are -CH 3 Or, -C 2 H 5 and A is CH or N; R a and R b each independently represents a hydrocarbon having 1 to 10 carbon atoms which may contain a substituent and in which hydrogen may be substituted with a halogen, R c is a hydrocarbon having 1 to 5 carbon atoms, in which hydrogen may be substituted with a halogen, p=3 to 30.

3. The method for producing a granulated powder according to claim 1, wherein the monohydrolytic group-type silane coupling agent is a silane coupling agent represented by the following formula (3): X-R 4 (3) [X is a hydrolyzable silyl group (-Si(OR 2 ) n (R 3 ) 3-n ) (n=1 to 3), R 2 and R 3 are -CH 3 Or, -C 2 H 5 and R 4 is a straight-chain or branched-chain hydrocarbon having 2 to 12 carbon atoms, which may contain a substituent and in which hydrogen may be replaced by a halogen.

4. The method for producing a granulated powder according to claim 2, wherein the hydrolyzable group-type silane coupling agent is a silane coupling agent represented by the following formula (3): X-R 4 (3) [X is a hydrolyzable silyl group (-Si(OR 2 ) n (R 3 ) 3-n ) (n=1 to 3), R 2 and R 3 are -CH 3 Or, -C 2 H 5 and R 4 is a straight-chain or branched-chain hydrocarbon having 2 to 12 carbon atoms, which may contain a substituent and in which hydrogen may be replaced by a halogen.

5. 5. The method according to claim 1, wherein the filler has a hydrophilic surface.

6. The method according to any one of claims 1 to 4, wherein the filler is a metal or a metal oxide.

7. 3 to 40 volume percent of a filler; A granulated powder comprising: 60 to 97 volume % of polytetrafluoroethylene powder; A granulated polytetrafluoroethylene powder containing not more than 1 part by mass of a polyhydrolyzable silane coupling agent and a monohydrolyzable silane coupling agent per 100 parts by mass of a total of a filler and the polytetrafluoroethylene powder.

8. The polytetrafluoroethylene granulated powder according to claim 7, wherein the polyhydrolyzable group type silane coupling agent is a bis-silane type silane coupling agent represented by formula (1) or a polymer type silane coupling agent containing a repeating monomer unit represented by formula (2). X-R 1 -X (1) [X is a hydrolyzable silyl group (-Si(OR 2 ) n (R 3 ) 3-n ) (n=1 to 3), R 2 and R 3 are -CH 3 Or, -C 2 H 5 and R 1 is a straight-chain or branched-chain hydrocarbon having 2 to 12 carbon atoms, which may contain a substituent and in which hydrogen may be replaced by a halogen. 【Chemistry 2】 [X is a hydrolyzable silyl group (-Si(OR 2 ) n (R 3 ) 3-n ) (n=1 to 3), R 2 and R 3 are -CH 3 Or, -C 2 H 5 and A is CH or N; R a and R b each independently represents a hydrocarbon having 1 to 10 carbon atoms which may contain a substituent and in which hydrogen may be substituted with a halogen, R c is a hydrocarbon having 1 to 5 carbon atoms, in which hydrogen may be substituted with a halogen, p=3 to 30.

9. The polytetrafluoroethylene granulated powder according to claim 7, wherein the monohydrolyzable silane coupling agent is a silane coupling agent represented by the following formula (3): X-R 4 (3) [X is a hydrolyzable silyl group (-Si(OR 2 ) n (R 3 ) 3-n ) (n=1 to 3), R 2 and R 3 are -CH 3 Or, -C 2 H 5 and R 4 is a straight-chain or branched-chain hydrocarbon having 2 to 12 carbon atoms, which may contain a substituent and in which hydrogen may be replaced by a halogen.

10. The polytetrafluoroethylene granulated powder according to claim 8, wherein the monohydrolyzable silane coupling agent is a silane coupling agent represented by the following formula (3): X-R 4 (3) [X is a hydrolyzable silyl group (-Si(OR 2 ) n (R 3 ) 3-n ) (n=1 to 3), R 2 and R 3 are -CH 3 Or, -C 2 H 5 and R 4 is a straight-chain or branched-chain hydrocarbon having 2 to 12 carbon atoms, which may contain a substituent and in which hydrogen may be replaced by a halogen.

11. The granulated powder according to any one of claims 7 to 10, having an average particle size of 200 to 800 μm.

12. The granulated powder according to any one of claims 7 to 10, wherein the filler has a hydrophilic surface.

13. The granulated powder according to any one of claims 7 to 10, wherein the filler is a metal or a metal oxide.

Citation Information

Patent Citations

  • JP1969022620Y1

  • Ryujonotetorafuruoroechirenjugotaitoryujono shinsuiseijutenzaitokaranaru gyoshushitaryujobutsunoseizoho

    JP1976000549A

  • Piezoelectric receiver

    JP1985021694A

  • Polytetrafluoroethylene granulate powder and method for producing the same

    JP2001220482A

  • Process for preparing filler-containing polytetrafluoroethylene powder for molding

    JP2002201287A